Theoretical and Methodological Perspectives on Higher Education Management and Transformation An advanced reader for PhD students - Pekkola, Elias; Kivistö, Jussi; Kohtamäki, Vuokko; Cai, Yuzhuo; Lyytinen, Anu (Tampere University Press, 2018)
As an interdisciplinary field of study, higher education research is still underdeveloped in terms of theoretical matureness and rigour. This book offers perspectives on how a range of methodological choices, theoretical approaches and conceptualisations from other disciplines can be successfully applied and utilised in the context of higher education. As a reader compiled of independent chapters, the book is particularly aimed at PhD students in the field of higher education administration. The book consists of three parts: I Methodological Approaches - examples for early career researchers; II Conceptual Approaches Utilised to Understanding University Transformation; and, III Scholarly Traditions Applied to Understand Universities and Academic Work. The first part highlights the importance of methods in research, and provides examples of academic dissertations with strong methodological groundings. In the second part, the authors provide theoretical and conceptual aids to analyse the transformation of higher education. The third part focuses on how traditional and well-established theoretical approaches can be applied to higher education settings in terms of, for example, research questions.